Cerebral Pulsatility Index Is Elevated in Patients with Elevated Right Atrial Pressure. Issue 1 (3rd July 2017) - Lahiri, Shouri; Schlick, Konrad H.; Padrick, Matthew M.; Rinsky, Brenda; Gonzalez, Nestor; Jones, Heather; Mayer, Stephan A.; Lyden, Patrick D.
ABSTRACT: BACKGROUND AND PURPOSE: Extracerebral venous congestion can precipitate intracranial hypertension due to obstruction of cerebral blood outflow. Conditions that increase right atrial pressure, such as hypervolemia, are thought to increase resistance to jugular venous outflow and contribute to cerebro‐venous congestion. Cerebral pulsatility index (CPI) is considered a surrogate marker of distal cerebrovascular resistance and is elevated with intracranial hypertension. Thus, we sought to test the hypothesis that elevated right atrial pressure is associated with increased CPI compared to normal right atrial pressure. METHODS: We retrospectively reviewed 61 consecutive patients with subarachnoid hemorrhage. We calculated CPI from transcranial Doppler studies and correlated these with echocardiographic measures of right atrial pressure. CPIs were compared from patients with elevated and normal right atrial pressure. RESULTS: There was a significant difference between CPI obtained from all patients with elevated right atrial pressure compared to those with normal right atrial pressure ( P < .0001). This finding was consistent in sensitivity analysis that compared right and left hemispheric CPI from patients with both elevated and normal right atrial pressure. CONCLUSION: Patients with elevated right atrial pressure had significantly higher CPI compared to patients with normal right atrial pressure. These findings suggest that cerebro‐venous congestion due to impaired jugular venous outflow may increase distal cerebrovascular resistance as measured by CPI. Since elevated CPI is associated with poor outcome in numerous neurological conditions, future studies are needed to elucidate the significance of these results in other populations.